Soccer national team of Kosovo (U19) in comparison with other players in this country with regards to anthropometric characteristics and body composition - Bjelica, D.; Gardasevic, J.; Masanovic, B.; Vasiljevic, I. (International Journal of Applied Exercise Physiology, 2020)
The aim of this research was to determine the differences between the young soccer players (U19) in a terms of anthropometric characteristics and body composition of two the most successful clubs and of national team in country of the Kosovo. The first sub-sample of the subjects was consisted of 13 soccer players of FC Pristina of the average age 17.77±.59. The second sub-sample was consisted of 15 soccer players of FC Feronikeli of the average age 18.07±.46. The last sub-sample of the examinees was consisted of 25 soccer players of Kosovo national team of which 18 players who are playing abroad, and the rest from domestic league, of the average age 17.68±.56. Anthropometric characteristics in the body composition were evaluated by a battery of 10 variables. The significance of the differences between the young soccer players in the anthropometric characteristics and variables for assessing body composition were determined by ANOVA and LSD Post Hoc test. The young soccer players of the two mentioned clubs and Kosovo national team have statistically significant differences in the two variables that estimate the body height and body weight. The players of Kosovo national team are significantly higher than other players, and have significantly more body weight than soccer players of FC Feronikeli. The results can be useful for coaches of the FC Pristina and FC Feronikeli for making a comparison of their soccer players with the young soccer players of the Kosovo national team, as well coaches from other clubs in Kosovo.